Exploring the Pharmacological Potential of Dantha Dhavana Drugs Mentioned in Brihat Thrayi and Laghu Thrayi in Terms of Their Rasapanchaka (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda have always approached health with prime focus on maintenance of health in a healthy individual prior to the concept of treatment of a diseased individual. This implies the necessity of various concepts of Ayurveda mentioned across various Samhitas like Brihatrayi’s and Laghutrayi’s namely Dinacharya, Ritucharya, Swasthavritta, Janapadoshwamsa etc. All these concepts mentioned helps an individual to maintain the healthy state and prevent any health deficit that could lead to the manifestation of a disease. Among the concept of Dinacharya or the regimens to be followed in daily life, Acharya mentions Danta dhavana mentioned to preserve and promote oral hygiene. Even though the concept is familiar, the drugs mentioned for its usage are specific according to each Acharyas. This article is aimed to provide an insight into the pharmacological potential of drugs that possesses Danta dhavana action mentioned in the Brihatrayi and Laghutrayi.